FUNGSI TARI NGAJAT LESUNG DI DESA SELUAS KECAMATAN SELUAS KABUPATEN BENGKAYANG - Pankarius Gagas Saputra; Ismunandar Ismunandar; Imma Fretisari (Universitas Tanjungpura, 2019)
AbstractThe background of this research was that there was a uniqueness in the way of using mortar/lesung in Ngajat Lesung dance at Seluas Village, which was by bitten but it also functioned as the guest reception dance (aesthetic presentation) and entertainment dance in Dayak Iban society. The purpose of this research were describing the function, entertainment,aesthetic presentation of Ngajat Lesung dance and describing the implementation design in Ngajat Lesung dance on the Art and Culture subject. The method ofthis research was descriptive method. Data collecting techniques were observation, interview, and documentation. The validity of the data testing techniques were extension of observation, and the source triangulation. The function of Ngajat Lesung dance was as the personal entertainment without distinguishing social strata, non-formal personal entertainment, and personal entertainment whose dance moves did not grip. The function of the Ngajat Lesung dance was as an aesthetic presentation on the night before the Gawai Batu DayakIban began and during the Gawai Batu. The Implementation Design of the results in this research was a Lessons Plan (RPP) which could be used as a guide for Art and Culture subject teachers onJunior High School (SMP). Keywords: Dayak Iban, Function of Dance, Ngajat Lesung Dance.